Perception des populations sur le rôle des aires protégées dans leur résilience face au changement climatique : cas du Parc National de la Marahoué (Centre-Ouest, Côte d’Ivoire). - Yves Adélani Olatoundji; Djakalia Ouattara; Yao Konan; Junior Ohouko (VertigO, 2021)
Protected areas represent a key tool to mitigate climate change, as they provide several ecosystem services to people, especially the surrounding communities. However, their multiple roles in adaptation or resilience to climate change are often overlooked. In addition, the ecosystem services they provide to populations are mostly unknown, which affects their appropriation by neighbouring communities and, therefore, their protection. Our study consists of evaluating the knowledge of local communities on the role played by the Ivorian Marahoue National Park (MNP) and the ecosystem services it can provide. More specifically, the study aims to question the surrounding communities on the importance of the MNP at the local and national level and the ecosystem services that it can provide as a regional biosphere. The results show that local populations have different perceptions of the role of the MNP, assets, and ecosystem services. However, knowledge is not evenly distributed among neighbouring communities. Teachers and those with higher levels of education better understand the roles of the MNP and have different knowledge about ecosystem services. Although a large part of the population wishes to be involved in the MNP management process, the majority believe that the management of the protected area is poor, and therefore its restoration is unnecessary. To better integrate the surrounding communities into the park's management processes, this research highlights the need to develop awareness-raising projects on the benefits and ecosystem services offered by the MNP at the local level.